2004
DOI: 10.1120/jacmp.v5i3.1982
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning and quality assurance for intensity‐modulated radiotherapy with dynamic multileaf collimator: Experience of the Pontificia Universidad Católica de Chile

Abstract: The objective of this paper is to present our experience in the commissioning and quality assurance (QA) for intensity-modulated radiotherapy (IMRT) using the dynamic multileaf collimator (dMLC), sliding window technique. The connectivity and operation between all IMRT chain components were checked on the Varian equipment. Then the following tests were performed: stability of leaf positioning and leaf speed, sensitivity to treatment interruptions (acceleration and deceleration), evaluation of standard field pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…In the literature there are two proposed methodologies to conduct the test: either by creating a uniform pattern with abutting fields (7,8) or by using specified intervals to irradiate a series of narrow bands. (9,10) In the first proposed method, the resulting image is checked for missed or overirradiated spots. In the second one, the width of the narrow bands is measured and checked for discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature there are two proposed methodologies to conduct the test: either by creating a uniform pattern with abutting fields (7,8) or by using specified intervals to irradiate a series of narrow bands. (9,10) In the first proposed method, the resulting image is checked for missed or overirradiated spots. In the second one, the width of the narrow bands is measured and checked for discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional method for two-dimensional (2D) checking of MLC leaf positions was to use film images of a dynamic MLC (DMLC) leaf pattern. 13,[20][21][22][23][24] Film images were either visually inspected or scanned, digitized, and contrast enhanced. 2 Visual inspection is a subjective and inaccurate method for checking the leaf pair alignment and uniformity of the gap widths.…”
Section: Introductionmentioning
confidence: 99%
“…Dynalog files have been tested 34 and used as reference in many studies on the leaf positioning accuracy. 8,22,23,[36][37][38] However, the validity of the data in Dynalog files strongly depends on the accuracy of leaf position readouts. Any possible drift in the encoder readings could be temporarily improved by the MLC re-initialization, 9 but it must be routinely checked by independent imaging methods.…”
Section: Introductionmentioning
confidence: 99%
“…One popular approach to treatment delivery system quality control is the use of machine log files (e.g., Varian Dynalog files). 5,[15][16][17][18][19][20][21][22] Machine log files offer a number of advantages such as the ability to streamline and automate QA processes, however, a number of recent studies have shown that log files are insensitive to some types of delivery errors. 16,23,24 This insensitivity arises from the fact that the parameters recorded by log files (i.e., MLC positions, gantry angle and dose fraction) are sourced from the linac control system itself and hence are not independent measurements.…”
Section: Introductionmentioning
confidence: 99%